The Effect of Service Quality on Customer Loyalty at BSI KCP Seunagan, Nagan Raya Regency - Nur Fajri Ifar; Siti Hajar; Ahmad Arkadius (LPPM Politeknik Aceh Selatan, 2023)
This study aims to determine the effect of service quality on customer loyalty at BSI KCP Seunagan Nagan Raya Regency. The dependent variable in this study is customer loyalty while the independent variable is service quality. The method used in this study is to use multiple linear regression. Based on the results of the study using the ANOVA test (F test) shows that the sig value <0.05, in other words H0 rejects, meaning that service quality affects customer loyalty BSI KCP Seunagan Nagan Raya Regency